2019
DOI: 10.3390/cryst9110572
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Geopolymers Synthesized from Fly Ash and Red Mud under Ambient Conditions

Abstract: Aluminosilicate gels form geopolymers and nanocrystalline zeolites which have comparable strength properties, making them a potential replacement for ordinary Portland cement. The study explores the use of two untreated industrial wastes, Class-F fly ash and red mud, for synthesizing geopolymeric material at ambient synthesis conditions. The high alkalinity present in the red mud was exploited for the dissolution of silica in the fly ash and red mud. The mechanical, mineralogical, microstructural, and pore cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The fibrous properties and pozzolanic properties of RHA contributed to a strength development of 65 MPa, with 63% CO 2 less energy-intensive outputs. Additionally, the contribution of biomass, e.g., bagasse ash, to geopolymer synthesis satisfied the making of medium-strength geopolymers, as reported by Rukzon and Chindaprasirt [21]. The delivered synthesis comprised of low, porous, medium-strength, complete waste and accelerated the cured geopolymer route to optimize the desired low-strength-based geopolymers.…”
Section: Geopolymer Synthesissupporting
confidence: 64%
See 1 more Smart Citation
“…The fibrous properties and pozzolanic properties of RHA contributed to a strength development of 65 MPa, with 63% CO 2 less energy-intensive outputs. Additionally, the contribution of biomass, e.g., bagasse ash, to geopolymer synthesis satisfied the making of medium-strength geopolymers, as reported by Rukzon and Chindaprasirt [21]. The delivered synthesis comprised of low, porous, medium-strength, complete waste and accelerated the cured geopolymer route to optimize the desired low-strength-based geopolymers.…”
Section: Geopolymer Synthesissupporting
confidence: 64%
“…The microstructural analysis provides evidence of the physical microstructure of geopolymer. This has been conducted by Koshy et al [21] on aluminium industrial waste, i.e., red mud and thermal power plant coal burnt i.e., fly ash, for micro structural geopolymers' characteristics, within varying ages of 7 days, 14 days, 21 days and 28 days. It is reported that, after 7 days of curing, fly ash showed a rounded but loose pattern, due to less reactivity of particles with alumino-silicate gel around them.…”
Section: Surface Morphological Characterization Through Scanning Electron Microscopy (Sem) For Engineered Geopolymer Concretementioning
confidence: 99%
“…Considering the small particle size and initial higher reactivity, red mud could be potentially used with other by-products to achieve synergy [7]. Due to the high alkalinity a combination of red mud with materials such as class F fly ash from this research could give good results when used in geopolymers [29]. Finally, the least reactive materials such as slags, if ground finely could serve as inert filler, contributing to the strength development by providing additional space for nucleation growth, or could be used to improve fire or wear resistance of concrete.…”
Section: Discussionmentioning
confidence: 93%
“…Hematite and Gibbsite are highly visible in red mud sample that also contains some amount of calcium carbonate. These non-reactive minerals, together with the low amount of amorphous phase, could negatively influence the strength development of red mud-based concrete [29]. Both fly ashes have a higher amount of amorphous phase, around 90%.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…CaCO 3 and Ca 2+ compounds [25]; stratlingite (C 2 ASH 8 ) and carbonates [26] (0.007~0.24%) 1-7 MPa [37]; / SEM [35]; XRD, FTIR, and TG/DTA [36][37][38]; XPS [41] ettringite, C-S-H and N-A-S-H [35]; aluminous C-S-H, C-A-S-H and 16 MPa (28 d) [64] As, Cu, Cr, and Cd [63], Cu, Zn, Cd, Pb, Fe, and Cr [65] XRD, FTIR, SEM, and TG [59][60][61]; SEM, XRD, Mid-Infrared spectroscopy (MIR), FTIR [62]; XRD, SEM, FTIR, or TG [63];…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%